It takes two to tango: Preserving daptomycin efficacy against daptomycin-resistant MRSA using daptomycin-phage co-therapy - Casey L. Madison; Anja S. J. Steinert; Corrin E. Luedeke; Neeka Hajjafar; Prakhar Srivastava; Andrew D. Berti; Arnold S. Bayer; Razieh Kebriaei (Microbiology Spectrum)
ABSTRACT Daptomycin (DAP) is a cyclic lipopeptide antibiotic that targets the cell membrane and is commonly used for the treatment of multidrug-resistant Staphylococcus aureus infections, especially methicillin-resistant strains (MRSA). Emergence of DAP resistance during DAP therapy is increasingly reported; however, the mechanisms by which resistance occurs are diverse. Using phages in combination with antibiotics is of high interest to circumvent antibiotic resistance, due to their minimal side effects, accessibility, and synergistic effects with antibiotics. Here, we have investigated the relationship between DAP resistance and sensitivity to phage Sb-1 in a cohort of 14 clinical MRSA strains. This cohort consists of four isogenic pairs (a clinical DAP-susceptible parent and its isogenic DAP-resistant variant isolated during DAP treatment), and three DAP-susceptible/DAP-resistant strain pairs are created by traditional serial passaging in the presence of increasing DAP concentrations. Efficiency of plating (EOP) and bacteriophage plaque sizes were recorded, and synergy between the antibacterial agents was tested using the phage-antibiotic combination (PAC) checkerboard method. Plaque sizes and EOP significantly increased (P = 0.019 and P = 0.008, respectively) as strains developed resistance to DAP. The PAC checkerboards conveyed less antagonistic patterns in DAP-resistant mutant strains compared with their DAP-susceptible counterparts. Antagonism was displayed in 71.4% (5/7) of the DAP-susceptible strains, while it was only present in 14.3% (1/7) of the DAP-resistant mutants. Transmission electron microscopy images showed significantly thicker cell walls in DAP-susceptible strains exposed to DAP monotherapy compared with either growth control or DAP-phage (P = 0.0002 and 0.0007, respectively). These data indicate increased sensitivity to phage Sb-1 concurrent with the emergence of DAP resistance.IMPORTANCEMultidrug-resistant Staphylococcus aureus is a threat to the health care system, especially cross-resistance between daptomycin (DAP) and glycopeptides through various mutations such as mprF (which is involved in the modification of membrane phospholipids in some bacteria) and yycG (part of a two-component regulatory system in bacteria that is important for regulating cell wall biosynthesis and other cellular processes) has been reported previously. Our current study shows adjunctive treatment with phage in DAP-resistant strains will lead to synergistic activity and larger phage plaque sizes, translating to elevated lytic performance. The addition of bacteriophage to standard-of-care antibiotic therapies for multidrug-resistant S. aureus infections has the potential to hinder, and possibly revert, resistance to antibiotics. Applying this strategy can potentially lead to the preservation of the current antibiotics. Verification of this salutary outcome in relevant ex vivo and in vivo models of endovascular infections is required to validate translatability.